2014 Workshop on Fault Diagnosis and Tolerance in Cryptography 2014
DOI: 10.1109/fdtc.2014.20
|View full text |Cite
|
Sign up to set email alerts
|

Clock Glitch Attacks in the Presence of Heating

Abstract: Fault attacks have been widely studied in the past but most of the literature describes only individual fault-injection techniques such as power/clock glitches, EM pulses, optical inductions, or heating/cooling. In this work, we investigate combined fault attacks by performing clock-glitch attacks under the impact of heating. We performed practical experiments on an 8-bit AVR microcontroller which resulted in the following findings. First, we identified that the success rate of glitch attacks performed at an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…These factors for the clock and voltage fault attacks include accuracy, development expenses, complexity of the system set-up, and user expertise. Below, we identify a list of features regarded in the literature as being the main ones for a hardware-based fault generator [11,19,27,29,[37][38][39][40][41]]:…”
Section: Preliminaries and Basic Conceptsmentioning
confidence: 99%
See 3 more Smart Citations
“…These factors for the clock and voltage fault attacks include accuracy, development expenses, complexity of the system set-up, and user expertise. Below, we identify a list of features regarded in the literature as being the main ones for a hardware-based fault generator [11,19,27,29,[37][38][39][40][41]]:…”
Section: Preliminaries and Basic Conceptsmentioning
confidence: 99%
“…There are various practical techniques for generating a faulty clock signal [11,17,19,27,29,[37][38][39][40][41]48,49]. All of the proposed methods call for a high-frequency clock signal, the so-called 'Nominal Clock' on the clock fault generator side.…”
Section: A Review Of Previously Proposed Clock Glitch Generatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…4) Combination of Voltage, Frequency, and Temperature Fault Injection: Zussa et al [16] demonstrated that overclocking, clock glitching, voltage glitching, underfeeding, and overheating exploit the same fault injection mechanism, which is the violation of a device's setup-time constraints. In addition, Korak et al [17], [25] showed overheating and voltage glitching improves the efficiency of clock glitching.…”
Section: A Hardware-controlled Fault Injection Techniquesmentioning
confidence: 99%